Analisis Prosedur Reimbursement Melalui Sistem Aplikasi Satria Keuangan Pada Dinas Kesehatan - Azizah, Siti Nur (Jurnal Akuntansi UMMI, 2022)
The allocation of funds from the Banyumas District Health Office comes from the State Revenue and Expenditure Budget (APBN) and the Regional Revenue and Expenditure Budget (APBD). The APBN and APBD funds are allocated in the form of Inventory Replacement (GU) or in the form of Reimbursement. The purpose of writing this final project is to find out whether the Reimbursement or GU procedure using the financial knight application system at the Banyumas District Health Office is in accordance with the applicable Standard Operating Procedures (SOP). The method used is primary and secondary data. The primary data were obtained from interviews, observations, and documentation. While secondary data obtained from books and other literature as a reference for writing the final project. The results of this study concluded that the Reimbursement or GU procedure using the financial knight application had been carried out correctly and efficiently according to the applicable SOP.